New taxa of the Meganola argentescens (Hampson, 1895) species group from China (Lepidoptera, Nolidae, Nolinae) - Hu, Yan-Qing; Wang, Min; Han, Hui-Lin (Zootaxa, 2017)
Meganola argentescens (Hampson, 1895) species group is consisted of four species, Meganola argentescens (Hampson, 1895), Meganola jinghongensis (Shao, Li & Han, 2009), two of which are described below (Meganola weixiensis sp. nov. and Meganola xui sp. nov.). The diagnostic external features of the species group are the silvery forewing ground color, the black or dark brown marking at medial line area before cell, the black or dark brown and striped marking at wing base along with costal margin, the shrinked valva medially, the long and cylindrical aedeagus with many spinulae at apex and vesica without cornuti in male genitalia. It is worth nothing that the so-called group is supposed by the external appearance of adult and configuration of male genitalia.